IMPORTANCE OF EVOLUTION OF PHRASAL VERBS AND THEIR HISTORY - Tairova, Shahnoza Bahromovna; Butunbayeva, Aziza Sayfullo Qizi (Innovative Development in Educational Activities, 2023)
The aim of this article is to supplement existing research on history of English phrasal verbs and its evolution by exploring fist versions till the present day. The periodization of languages into ‘old’, ‘middle’ and ‘new’ periods, or even more subtle distinctions, is a tricky issue. However, phrasal verbs present status and their position in verbal lexicon of contemporary English demand to study their periods of establishing. This work highlights and give instruction of how used phrasal verbs in past time.